The Analysis and Examination of Keyhan Ghazvini Interpretation Method - Abbas Mosalaiipour; Yahya Mir Hosseini (آموزه‌های قرآنی)
One of the Quran well-known interpretive methods is the mystical interpretation with a long period record besides the other methods such as theological, philosophic, jurisprudential, literary methods. In 14th century this interpretative attitude took place in two different paths: classical and non-classical. The most important goal of this paper is the examination of Abbas Ali Keyvan Ghazvini’s interpretative method. His attitude is mystical and for instance of its differences from the prior mystical interpretations; we should regard it as one of the first non-classical mystical interpretations. The most important characteristic of interpretative method of Ghazvini is excessive attention to the external appearance of the words in comparison with the prior ones, lack fidelity to the antecedents’ discourses, not applying to the infallibles’ traditions and the companions and an approximate approach between Islamic schools. These different attitudes and approaches to the Quran and interpretation which have differentiated him from his contemporaries.